THE ROLE OF CONTEXT IN KNOWLEDGE AND INNOVATION STRATEGIES: GLOBAL VS. EGYPTIAN SAMPLE - Marina Apaydin; Rehab Wahsh (European Scientific Journal, ESJ, 2014)
Management research on knowledge and organizational innovation (OI) is a vast field which covers numerous topics and occurs at multiple levels of analysis (Crossan & Apaydin, 2010). However, the role of context in this research has been underexplored. The importance of inclusion of context in management research has been repeatedly highlighted by Tsui and colleagues (2004) with reference to Chinese context. This paper investigates the role of context in development and implementation of knowledge and innovation strategies by benchmarking an Egyptian sample (8 companies) with the Global Sample (68 companies), using the Innovation Audit Instrument developed based on the Comprehensive Model of OI (Crossan & Apaydin, 2010). The results indicate that the Egyptian companies lag behind the Global Sample in all aspects of the determinants of OI: leadership, managerial levers and business processes. Their innovation strategies are based on exploitation rather than on exploration. Also, only one company was practicing Sustainable innovation strategy (as defined in Zona, 2009), while most had no explicit innovation approach. Increasing company awareness about the comprehensive model of innovation and the imperative of an explicit innovation strategy is one of the managerial implications of this study.